Dynamics of Evolutionary Engineering: Revolutionary Biomimicry Applications - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2017)
The current article is a research article on the concept of evolutionary engineering concept of biomimicry applications. It explores some of the current applications of the natural or biologically inspired processes and designs which have revolutionized the way products and processes have been existing and seen so far. It also lays down the basis for numerous possibilities of future applications which are based on similar principles and practices of applications, process and pattern implementation. This research article includes the literature of some eminent discoveries made in the recent past and also connects withÂ  real life applications in the present scenario. The relation between the co-existence of biological processes and human adaptability can be visualized from the instances discussed.